SOCIAL MEDIA NETWORKING AND SELF-ESTEEM AMONG JUNIOR HIGH SCHOOL STUDENTS - Dumawal, Alexander; GENEVIVE D. GARCIA (Studies in Technology and Education, 2024)
In the digital era, the influence of social networking on junior high school students is a matter of growing interest and concern. This study aimed to investigate the extent of social networking and its relationship with self-esteem among junior high school students in Cordon, Isabela, for the School Year 2023-2024. The research employed a descriptive-correlational design, gathering data from 359 students using the Social Networking Usage Questionnaire and the Rosenberg Self-Esteem Scale. Results revealed extensive social networking usage for various purposes, highlighting its role in communication, information sharing, and academic collaboration. Additionally, the study unveiled nuanced levels of self-esteem among respondents, with both positive and negative self-evaluations present. Correlational analysis showed diverse associations between social networking behaviors and dimensions of self-esteem, emphasizing the complex interplay between online activities and self-perception. These findings underscore the need for holistic approaches integrating digital literacy, psychological support, and social-emotional learning to promote positive self-esteem and well-being among students navigating the digital landscape. Overall, this study contributes to a better understanding of social networking dynamics and their implications for adolescent development and education. By addressing these issues, educators, parents, and policymakers can develop informed strategies to support students in cultivating a healthy relationship with social media while fostering their overall well-being and academic success.